Analysis of nanofiber-based La0.2Sr0.8TiO3–Gd0.2Ce0.8O1.9 electrode kinetics. Issue 62 (18th October 2018) - Wang, Yuwei; Zhao, Erqing; Fan, Liquan; Hu, Qianjun; Liu, Xijun; Li, Yufeng; Xiong, Yueping
Abstract : NF-LST–GDC shows lower ohmic resistance (determined using CI and EIS techniques), smaller potential drop and better kinetics than NP-LST–GDC. Abstract : For the sake of comparison, a single cell with nanofiber-based LST–GDC composite anode (Cell-1) and a single cell with nanoparticle-based LST–GDC composite anode (Cell-2) are fabricated, respectively. The electrolyte ohmic resistances of the LST–GDC composite anode side half-cells are determined by an AC resistance measurement. Current interrupt is applied to measure the ohmic resistance of the half-cells. Combined with V – I characteristics, the influences of the potential drops caused by electrolyte ohmic resistance, electrode ohmic resistance and electrode electrochemical reaction on the cell kinetics are investigated. Under a current density of 0.6 A cm −2 at 850 °C, for the nanofiber-based LST–GDC composite anode (NF-LST–GDC), the electrode ohmic potential drop is 0.007 V and the potential drop caused by the electrode electrochemical reaction is 0.080 V. While for the nanoparticle-based LST–GDC composite anode (NP-LST–GDC), the corresponding potential drops are 0.159 V and 0.246 V, respectively. Both the potential drops of the former are lower than those of the latter. The kinetics of Cell-1 is greater than Cell-2, i.e., the kinetics of NF-LST–GDC is greater than that of NP-LST–GDC.